Enhancing Student Learning Motivation: A Problem-Based Learning Approach with Flipped Classroom Model in Distance Learning Design - Setiawan, M. Eval; Laswadi, Laswadi; Hermawan, Candra; Purnawati, Wilda (Unnes Science Education Journal, 2023)
This research aims to increase students’ learning motivation by developing a Problem-Based Learning learning design using the flipped classroom model. This research uses an approach that is part of non-experimental quantitative research. The sampling technique used purposive sampling. This research was measured using a learning motivation observation sheet in the form of a motivation rubric. Increased motivation was analysed based on a questionnaire based on the ARCS rubric. This research shows increased motivation in the learning process with the flipped classroom model and problem-based learning design. At the attention stage, there was an increase in student motivation by 13% from the first meeting to the second meeting and a rise of 6% from the second meeting to the third meeting. In the relevance aspect, there was an increase of 26% from meeting one to meeting two and 3% from meeting two to meeting three. Then, part of confidence, from the first to the second meeting, there was an increase of 9%, and from the second to the third meeting, it increased by 10%. Finally, in the aspect of satisfaction from meeting one to meeting two, there was an increase of 9%. Moreover, from meeting two to meeting three, there was an increase of 12%. It was concluded that the average increase in student motivation from the first lesson to the third lesson was 3% to 13%. In the future, further attention is needed on the affective and psychomotor aspects.